2022
DOI: 10.1038/s41598-022-18195-8
|View full text |Cite
|
Sign up to set email alerts
|

The effects of vitamin B12 supplementation on metabolic profile of patients with non-alcoholic fatty liver disease: a randomized controlled trial

Abstract: The present study is the first effort to evaluate the effects of vitamin B12 supplementation on the serum level of liver enzymes, homocysteine, grade of hepatic steatosis, and metabolic profiles in patients with non-alcoholic fatty liver disease (NAFLD). Forty patients with NAFLD were enrolled in a double-blind placebo-controlled trial to receive either one oral tablet of vitamin B12 (1000 µg cyanocobalamin) or a placebo per day for 12 weeks. We investigated serum levels of homocysteine, aminotransferases, fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 44 publications
0
11
1
Order By: Relevance
“…Therefore, it does not necessarily imply that higher levels of serum vitamin B12 is due to a higher intake. A recent randomized controlled trial indicated that vitamin B12 supplementation significantly decreased serum levels of homocysteine compared to placebo, while no significant difference was revealed in between-group comparisons for fasting blood glucose, malondialdehyde, and liver steatosis ( 55 ). Because this study was unable to support our findings, further studies with different doses will reveal additional evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it does not necessarily imply that higher levels of serum vitamin B12 is due to a higher intake. A recent randomized controlled trial indicated that vitamin B12 supplementation significantly decreased serum levels of homocysteine compared to placebo, while no significant difference was revealed in between-group comparisons for fasting blood glucose, malondialdehyde, and liver steatosis ( 55 ). Because this study was unable to support our findings, further studies with different doses will reveal additional evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary supplementation with folate and vitamin B 12 alleviates steatohepatitis by promoting the enzymatic conversion of homocysteine [180]. A randomized controlled trial also showed the beneficial effects of vitamin B 12 supplementation in patients with MAFLD [181]. However, reports about the relationship between vitamins B 5 and B 7 and MAFLD are very limited.…”
Section: Vitamin B Metabolism and Mafldmentioning
confidence: 99%
“…This affects the signaling pathway in response to sterols, and as a consequence, the progression of NAFLD occurs [ 319 ]. In this way, the daily administration of 1000 µg of cyanocobalamin for 3 months in NAFLD patients decreased the serum concentration of homocysteine [ 320 ]. In NAFLD patients, by administering Vitamin B12, the serum concentration of homocysteine decreased significantly.…”
Section: Vitamins With Antioxidant Activity In Nafldmentioning
confidence: 99%
“…In NAFLD patients, by administering Vitamin B12, the serum concentration of homocysteine decreased significantly. Therefore, Vitamin B12 supplementation exerts therapeutic effects regarding the pathology of NAFLD [ 320 ]. Moreover, in NAFLD pathology, it has been observed that MDA, which is a marker of lipid peroxidation, is always increased [ 321 ].…”
Section: Vitamins With Antioxidant Activity In Nafldmentioning
confidence: 99%